2014
DOI: 10.1016/j.tics.2013.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Growing pains and pleasures: how emotional learning guides development

Abstract: SUMMARY The nervous system promotes adaptive responding to myriad environmental stimuli by ascribing emotion to specific stimulus domains. This affects the salience of different stimuli, facilitates learning, and likely involves the amygdala. Recent studies suggest a strong homology between adaptive responses that result from learning and those that emerge during development. As in motivated learning, developmental studies have found the salience of different classes of stimuli (eg peers) undergoes marked fluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 98 publications
2
32
0
1
Order By: Relevance
“…This analysis resulted in increased activity in lateral PFC and SPC, a network typically related to learning and cognitive control, as well as dorsal mPFC, IFG, insula and amygdala, related to mentalizing and emotional processing (Blakemore, 2008;Nelson and Guyer, 2011;Nelson et al, 2014;Peters et al, 2014). Within the process of peer feedback, learning and cognitive control areas may be involved to regulate own actions and adapt to the opinions or behaviors of others, which is typically associated with increased activity in lateral PFC and SPC .…”
Section: Discussionmentioning
confidence: 99%
“…This analysis resulted in increased activity in lateral PFC and SPC, a network typically related to learning and cognitive control, as well as dorsal mPFC, IFG, insula and amygdala, related to mentalizing and emotional processing (Blakemore, 2008;Nelson and Guyer, 2011;Nelson et al, 2014;Peters et al, 2014). Within the process of peer feedback, learning and cognitive control areas may be involved to regulate own actions and adapt to the opinions or behaviors of others, which is typically associated with increased activity in lateral PFC and SPC .…”
Section: Discussionmentioning
confidence: 99%
“…The ability of a person to perceive the significance of an environmental stimulus and to generate rapidly an appropriate response is an important aspect of optimizing behavior and performance (Nelson, Lau, & Jarcho, 2014). Emotions have an important role in this process, serving as modulators between the internal state of the person and the stimulus or context in which they are encountered (Nelson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Emotions have an important role in this process, serving as modulators between the internal state of the person and the stimulus or context in which they are encountered (Nelson et al, 2014). Emotions can be described as ''dispositions to action'', reflecting central activation and preparation for action (Lang & Bradley, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Recent conceptual frameworks view the adolescence-associated increase in 'emotionality' and 'sociality' as facilitating learning for specific, relevant (socio-emotional) experiences. Protracted maturation of neurocognitive abilities may enable individuals to be more flexible in their behavioral responses and adapt rapidly to changing social contextual demands (e.g., Crone and Dahl, 2012;Nelson et al, 2014). Following this line of thought, it has been suggested that interventions implemented at developmentally-sensitive junctures may yield more powerful and sustained therapeutic benefits (Cohen Kadosh et al, 2013).…”
Section: Are There Unique Learning Opportunities During Adolescence?mentioning
confidence: 99%
“…Instead, most recent syntheses of the data on brain-behavior relationships in adolescence describe this period as a time of flexibility and adaptation during which the teenage brain is specifically receptive to certain socially relevant experiences (e.g., Crone and Dahl, 2012;Nelson et al, 2014). The unique maturational schedule and sensitivities motivate and enable the adolescents to learn about social interactions and further develop competencies needed to navigate the world independently.…”
Section: Are There Unique Learning Opportunities During Adolescence?mentioning
confidence: 99%